2000
DOI: 10.1212/wnl.55.6.773
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon characteristics associated with mortality and morbidity following carotid endarterectomy

Abstract: More years since licensure and very low patient volume are associated with worse patient outcomes following CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 54 publications
6
84
1
5
Order By: Relevance
“…A progressive improvement of scores from resident to fellows to practicing surgeons supports the evidence that judgment improves through training, peaks shortly after training, and then begins to plateau or decline. This has been shown in several studies by demonstrating an increase in mortality of patients undergoing cardiac procedures with increasing years of practice of the primary surgeon (Hartz et al 1999;O'Neill et al 2000). Similar findings of increased mortality is also seen in a study of outcomes of acute myocardial infarction that showed an increase of 0.5% mortality for every year since the physician graduated from medical school (Norcini et al 2000).…”
Section: Discussionsupporting
confidence: 54%
“…A progressive improvement of scores from resident to fellows to practicing surgeons supports the evidence that judgment improves through training, peaks shortly after training, and then begins to plateau or decline. This has been shown in several studies by demonstrating an increase in mortality of patients undergoing cardiac procedures with increasing years of practice of the primary surgeon (Hartz et al 1999;O'Neill et al 2000). Similar findings of increased mortality is also seen in a study of outcomes of acute myocardial infarction that showed an increase of 0.5% mortality for every year since the physician graduated from medical school (Norcini et al 2000).…”
Section: Discussionsupporting
confidence: 54%
“…10 For studies specifically of surgical performance, there are also other reports showing that more years of experience are associated with worse patient outcomes following carotid endarterectomy, coronary artery bypass surgery, and pancreatectomy. [4][5][6] In contrast, one study reported that worse outcomes were observed for patients of young surgeons undergoing high-complexity alimentary tract surgery. 7 Although our study did not address the potential mechanisms responsible for the relationship between surgeon age and operative outcomes of primary RRD surgery, several possibilities might explain this effect.…”
Section: Resultsmentioning
confidence: 99%
“…4 Other studies also showed that more years of experience were associated with worse patient outcomes following carotid endarterectomy and coronary artery bypass surgery. 5,6 On the other hand, it is generally assumed that the knowledge, skills, and experience accumulated by physicians during years of practice may result in better clinical capabilities. 2 One report also suggested that surgeon youth and inexperience were more important risk factors for surgical mortality.…”
Section: Introductionmentioning
confidence: 99%
“…O'Neill et al [17] studied the relationship between years since licensure of the surgeon (and other factors) and death, or complications short of death, for the procedure of carotid endarterectomy. The study included 12,725 operations in 284 hospitals.…”
Section: Remoteness Of Educationmentioning
confidence: 99%